Investing more in universal social protection: Filling the financing gap through domestic resource mobilization and international support and coordination - Mira Bierbaum; Valérie Schmitt (International Labour Organization (ILO), 2022)
Large and persistent gaps in social protection coverage, comprehensiveness and adequacy are linked to many barriers, including high levels of informality, institutional fragmentation of the social protection system and significant financing gaps for social protection in a context of limited fiscal space. The latter have been further exacerbated by the impact of the COVID-19. Against this background, this paper discusses the magnitude and urgency of the challenge of filling social protection financing gaps and the options for achieving this. Options exist even in low-income countries, including by broadening the tax base; tackling tax evasion and building fair and progressive tax systems together with a sustainable macroeconomic framework; duly collecting social security contributions and tackling non-payment or the avoidance of social security contributions; reprioritizing and reallocating public expenditure; and eliminating corruption and illicit financial flows. National social protection systems should be primarily financed from domestic resources; however, for countries with limited domestic fiscal capacities or countries facing increased needs due to crises, natural disasters or climate change, international financial resources, in combination with technical assistance, could complement and support domestic resource mobilization for social protection. Furthermore, more dialogue and coherence need to be achieved between international financial and development institutions to avoid contradictory policy advice on the level and nature of investment in social protection. Finally, international cooperation, such as on tax matters or debt restructuring, is needed to create an environment that facilitates domestic resource mobilization.
Keywords: I3; H3; H53; H55; 330; social protection; social security systems; social protection floors; social security contributions; public expenditure; fiscal space; social protection financing; solidarity; domestic resource mobilization; official development assistance (ODA); developing countries; Sustainable Development Goals (SDGs)